Tips for Integrating Land and Wildlife Management: Quail in Cattle Country - William M. Giuliano; Lauren Watine (EDIS)
This 2-page fact sheet provides specific tips to improve quail habitat in cattle country that focus on diversifying the plant species and structural composition and increasing early successional communities dominated by herbaceous plants. Written by William M. Giuliano and Lauren Watine and published by the UF Department of Wildlife Ecology and Conservation, January 2013.